A Minority Stress-Emotion Regulation Model of Sexual Compulsivity Among Highly Sexually Active Gay and Bisexual Men. - Pachankis, John E; Rendina, H Jonathon; Restar, Arjee; Ventuneac, Ana; Grov, Christian; Parsons, Jeffrey T (Health psychology : official journal of the Division of Health Psychology, American Psychological Association, 2014)
Objective: Sexual compulsivity represents a significant public health concern among gay and bisexual men, given its co-occurrence with other mental health problems and HIV infection. The purpose of this study was to examine a model of sexual compulsivity based on minority stress theory and emotion regulation models of mental health among gay and bisexual men. Method: Gay and bisexual men in New York City reporting at least nine past-90-day sexual partners (n = 374) completed measures of distal minority stressors (i.e., boyhood gender nonconformity and peer rejection, adulthood perceived discrimination), hypothesized proximal minority stress mediators (i.e., rejection sensitivity, internalized homonegativity), hypothesized universal mediators (i.e., emotion dysregulation, depression, and anxiety), and sexual compulsivity. Results: The hypothesized model fit the data well (RMSEA = 0.05, CFI = 0.98, TLI = 0.95, SRMR = 0.03). Distal minority stress processes (e.g., adulthood discrimination) were generally found to confer risk for both proximal minority stressors (e.g., internalized homonegativity) and emotion dysregulation. Proximal minority stressors and emotion dysregulation, in turn, generally predicted sexual compulsivity both directly and indirectly through anxiety and depression. Conclusions: The final model suggests that gay-specific (e.g., internalized homonegativity) and universal (e.g., emotion dysregulation) processes represent potential treatment targets to attenuate the impact of minority stress on gay and bisexual men's sexual health. Tests of interventions that address these targets to treat sexual compulsivity among gay and bisexual men represent a promising future research endeavor. (PsycINFO Database Record (c) 2014 APA, all rights reserved).